Clinical stabilisation with lacosamide of mood disorder comorbid with PTSD and fronto-temporal epilepsy - Cuomo, Ilaria; Kotzalidis, Georgios D.; De Filippis, Sergio (Acta Biomedica Atenei Parmensis, 2017)
Background and aim of the work. Mood disorders are often complicated by comorbidity with epilepsy. Anxiety and personality disorders may worsen prognosis and treatment outcome. Lacosamide has been recently introduced as adjunctive treatment for partial epilepsy. Its mechanism consists of selective slow inactivation of voltage-gated sodium channels, thus promoting an extended stabilisation of cell membranes. Antiepileptic drugs have been largely used since the 1950s in psychiatry as mood stabilisers due to their membrane stabilising and anti-kindling effects. Like lithium, antiepileptic drugs are first choice treatment for Bipolar and Cyclothymic Disorders. Methods. We tested the efficacy of the most recent antiepileptic medication, lacosamide, in a patient with simultaneously occurring cyclothymic disorder, severe post-traumatic stress disorder, and fronto-temporal epilepsy. Lacosamide was titrated up to 200 mg/day, added on ongoing 750 mg/day lithium, 15 mg/day oral aripiprazole then switched to 400 mg/month long-acting aripiprazole, and 2 mg/day N-desmethyldiazepam. Results. We observed EEG normalisation one month later, along with reduced anxiety and an additive effect to lithium-induced stabilisation of mood fluctuations since the second week of lacosamide addition. Conclusions. Further studies with this drug in the bipolar spectrum are warranted.